POLA PERJALANAN WISATA GASTRONOMI DI KAWASAN TANAH ABANG JAKARTA PUSAT - Hasni Azmi Hazym; Dewi Turgarini; Dias Pratami Putri (JURNAL KEPARIWISATAAN, 2023)
DKI Jakarta, as the national capital and center of government, has its tourist attractions, one of which is gastronomic tourism. One area that has the potential for gastronomic tourism is the Tanah Abang area. Even though it is known as a shopping center, Tanah Abang also has traditional food, which has the potential as a gastronomic tour that can become a tourist attraction. There are several conventional and well-known food places in the Tanah Abang area; these places can become a gastronomic tourist attractions. The famous foods in Tanah Abang are uduk rice, ase porridge, and soto betawi. However, many do not know this potential. This study aims to analyze the potential for gastronomic tourism in the Tanah Abang area and to make patterns of gastronomic tourism trips. This study uses qualitative research methods using observation and interview techniques. Researchers found three places to eat to fit the travel pattern: Ase Bang Lopi Porridge, Soto Betawi H. Umar Idris, and Nasi Uduk Kebon Kacang Puas Hati Ibu Tati. The travel pattern obtained is a Complex Neighborhood with adequate accessibility. Â